Investigating the association between social participation and all-cause mortality risk among Chinese middle-aged and older adults - Zhengxing Xu; Xuehui Gan; Jiaxin Zeng; Peijing Yan; Chao Yang (Frontiers in Public Health)
ObjectiveWhile the association between social participation and all-cause mortality has been investigated to some extent, the link remains inconclusive, especially in China. This study aimed to investigate the association between social participation and all-cause mortality among middle-aged and older adult people in China.MethodsUsing data from the China Health and Retirement Longitudinal Study, and altogether 15,883 participants were included. The Cox proportional hazards regression model was used to assess the relationship between social participation and all-cause mortality, and subgroup analyses were conducted by age (< 60 years, ≥ 60 years) and sex.ResultsWith a median follow-up of 9.01 years, 2,175 participants developed deaths. Results from multivariable Cox regression modeling showed participants who participated in social activities had an all-cause risk of death of 0.88 (HR = 0.88, 95% CI: 0.78, 0.99) compared with those who did not. Further analyses showed that compared with participants with no social participation, those with 1 item of social participation had an all-cause mortality risk of 0.93 (HR = 0.93, 95% CI: 0.81, 1.06), and those with ≥ 2 items were 0.77 (HR = 0.77, 95% CI: 0.64, 0.94). In addition, subgroup analyses showed no age (Pinteraction = 0.571) or sex (Pinteraction = 0.440) differences in the relationship between the both.ConclusionOur results suggest social participation is an independent protective factor for all-cause death among middle-aged and older adult people in China. Active social participation helps to reduce the risk of death.